DIRECTIVE ILLOCUTIONARY ACTS FOUND IN “THE GUILTY” MOVIE 2021 - Arini, Ni Kadek Ayu Arini; Komang Dian Puspita Candra (ID Solutions, 2024)
The article embarks on an in-depth exploration of the diverse directive illocutionary acts depicted in the 2021 film